2015
DOI: 10.1111/jan.12740
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' views of patient participation in nursing care

Abstract: Nurses have a crucial role in promoting patient participation. Through acknowledging and enabling participation, nurses may facilitate patient participation in a range of nursing activities. The nurse's role in enacting participation is complex, having to accommodate each patient's risks and characteristics, highlighting the need for good assessment skills. Education, policy and research strategies are essential to foster nurses' pivotal role in patient participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 92 publications
2
83
0
6
Order By: Relevance
“…This is in line with many other studies showing that an optimal level of involvement depends on both users and professionals having adequate time to build relationships and share knowledge (Angel & Frederiksen, 2015; Leske, Strodl, & Hou, 2012; Rise et al, 2013; Sahlsten et al, 2009; Tobiano et al, 2015). On the other hand, the users’ often complex life challenges and conditions were described as a potential hindrance for user involvement, which is in accordance with other studies pointing out that users’ physical and mental capabilities, severe illness and poor health can impede involvement (Angel & Frederiksen, 2015; Longtin et al, 2010; Rise et al, 2013; Solbjør, Rise, Westerlund, & Steinsbekk, 2013; Tobiano et al, 2015) and health behaviour change (Abildsnes et al, 2017, 2016; Følling et al, 2015). In addition, our findings showed that the building of a trustful relationship and individualization of the service was disturbed by the use of standardized forms which interrupted the communication process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with many other studies showing that an optimal level of involvement depends on both users and professionals having adequate time to build relationships and share knowledge (Angel & Frederiksen, 2015; Leske, Strodl, & Hou, 2012; Rise et al, 2013; Sahlsten et al, 2009; Tobiano et al, 2015). On the other hand, the users’ often complex life challenges and conditions were described as a potential hindrance for user involvement, which is in accordance with other studies pointing out that users’ physical and mental capabilities, severe illness and poor health can impede involvement (Angel & Frederiksen, 2015; Longtin et al, 2010; Rise et al, 2013; Solbjør, Rise, Westerlund, & Steinsbekk, 2013; Tobiano et al, 2015) and health behaviour change (Abildsnes et al, 2017, 2016; Følling et al, 2015). In addition, our findings showed that the building of a trustful relationship and individualization of the service was disturbed by the use of standardized forms which interrupted the communication process.…”
Section: Discussionsupporting
confidence: 89%
“…However, the responsibility to deliver evidence-based or high-quality care, together with respecting service users’ right to make decisions, is sometimes described as conflicting (Shortus, Kemp, McKenzie, & Harris, 2013; Solbjør & Steinsbekk, 2011). Ensuring high-quality care is described as an argument for limiting user involvement and for professionals to decide and to exert control over patient care (Larsson, Liljedahl, & Gard, 2010; Shortus et al, 2013; Solbjør & Steinsbekk, 2011; Tobiano, Bucknall, Marshall, Guinane, & Chaboyer, 2015; Tobiano, Marshall, Bucknall, & Chaboyer, 2016), valuing professional knowledge above user knowledge (Solbjør & Steinsbekk, 2011). Although actively involved patients were considered valuable to enrich the professionals’ work, it is also looked upon as time-consuming and increasing the workload (Arnetz, Winblad, Arnetz, & Höglund, 2008; Arnetz & Zhdanova, 2015; Solbjør & Steinsbekk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…22 An Australian study highlights the importance of nurses sharing the responsibility for patient care with the family, empowering them to increase their participation. 7 Nevertheless, studies suggests that it is still difficult for nurses to relinquish power over care, so that they still maintain paternalistic attitudes in the care practice and establish a vertical relationship, based on resistance to insertion of the family. 10,15 Some limitations of the study can be pointed out due to the very qualitative nature of the research, since it is restricted to the space of experiences and the subjects involved.…”
Section: Discussionmentioning
confidence: 99%
“…6 Given the current statistics in relation to the increase in the number of adverse events, another study pointed out that effective participation by patients and family members in care together with the health team has contributed to the patient safety process. 7 In Brazil, the Child and Adolescent Statute (ECA) regulation guarantees permanence of a full-time companion during child hospitalization. Given this, it is imperative that the health team direct attention to the family needs, safely extending the object of nursing care to the newborn and family dyad.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of engagement can improve the relationship between healthcare professionals, patients and families in the context of person-centred care, for example, shared decision-making [7] [8] and self-management [9]. Research on person-centred care and related concepts such as person-centredness [10], patient-centred care [11], patient-close care and patient focus has grown rapidly [12], in different contexts, e.g., mental health [10], medical wards [13] and obstetric care [14]. Systematic development of a PS culture is necessary because inadequate quality of care leads to human suffering [15].…”
Section: Introductionmentioning
confidence: 99%